2020
DOI: 10.1177/1087054720925882
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-Enhanced Behavioral Parent Training for Clinic-Referred Families of Children With ADHD: A Randomized Controlled Trial

Abstract: Objective: This study evaluated the efficacy of a mindfulness-enhanced behavioral parent training (BPT) group program compared to standard BPT in families of children with ADHD. Method: Parents ( N = 63) of children (aged 6–11) diagnosed with ADHD were randomly assigned to either mindful or standard BPT, and participated in 12 weekly 2-hr group sessions. Parents completed a series of questionnaires assessing mindful parenting, parenting stress, harsh discipline practices, behavioral dysregulation, and child AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(58 citation statements)
references
References 59 publications
(68 reference statements)
1
36
0
4
Order By: Relevance
“…Furthermore, three studies from the current review found small effect size improvements to child behavior despite nil to negative effect size changes for parent mindfulness (Lo et al, 2019 , 2020 ; Zhang et al, 2017 ). Such findings have been replicated by other researchers (Mah et al, 2020 ), and raise questions about underlying mechanisms of change. It is possible that (1) parents from the studies reviewed improved their parenting style, and that this led to changes in child behavior, regardless of changes in parental mindfulness; (2) the Chinese version of the IM-P used by the three studies above is not culturally sensitive, and changes in parental reactivity and mindfulness correlate highly, as found by previous studies (Brown & Ryan, 2003 ); and/or (3) there are multiple pathways to change involved in MPPs.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Furthermore, three studies from the current review found small effect size improvements to child behavior despite nil to negative effect size changes for parent mindfulness (Lo et al, 2019 , 2020 ; Zhang et al, 2017 ). Such findings have been replicated by other researchers (Mah et al, 2020 ), and raise questions about underlying mechanisms of change. It is possible that (1) parents from the studies reviewed improved their parenting style, and that this led to changes in child behavior, regardless of changes in parental mindfulness; (2) the Chinese version of the IM-P used by the three studies above is not culturally sensitive, and changes in parental reactivity and mindfulness correlate highly, as found by previous studies (Brown & Ryan, 2003 ); and/or (3) there are multiple pathways to change involved in MPPs.…”
Section: Discussionsupporting
confidence: 58%
“…Our current understanding could be elucidated further through fine-grained analysis of the components of leading MP programs (e.g., Mindful Parenting) and MiBPs, alongside exploration of multiple mediators and moderators. For example, a recent study distinguished between parents’ use of informal moment-to-moment mindfulness in their parenting (open monitoring) versus formal meditation practice (focused attention) (Mah et al, 2020 ). Consistent with previous research, they found that although parents used informal mindfulness more regularly, it was increased use of formal meditational practice during the program that was associated with greater reductions in harsh parenting (Carmody & Baer, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Within SDT, there is growing literature relating mindfulness with reduced reactivity, lower stress appraisals, and more values-consistent behaviors under distressing situations (Donald et al, 2016; Schultz & Ryan, 2015). In this line, research among parents of children referred to mental health care has shown that pre-post changes in parents’ mindfulness are linked with a reduction in parental stress and an improvement of their own and their children’s psychological outcomes (Mah et al, 2020; Meppelink et al, 2016; Potharst et al, 2018).…”
Section: The Intervening Role Of Autonomy-support and Psychological C...mentioning
confidence: 99%
“…Finally, family therapists may also do well to help avoidant and anxious parents improve their ability to regulate their emotions Parents' good mood can reduce the frequency of conflict with teenagers. Helpful interventions may include programs that teach mindfulness to reduce harsh parenting (Mah et al, 2020 ) and train parents in behaviors that promote healthy parent–adolescent attachment.…”
Section: Discussionmentioning
confidence: 99%